Simulating Change in Cultural Landscapes: The Integration of Historic Landscape Characterisation and Computer Modelling. (2nd July 2020) - Erdoğan, Nurdan; Carrer, Francesco; Tonyaloğlu, Ebru Ersoy; Çavdar, Betül; Varinlioğlu, Günder; Şerifoğlu, Tevfik Emre; Jackson, Mark; Kurtsan, Kübra; Nurlu, Engin; Turner, Sam
ABSTRACT: More than 80 per cent of the world's landscapes are influenced significantly by human activities, and current land-use and land cover trends are likely to increase the rate of landscape change at a significant rate in the near future. To manage and guide landscape change, and an advocacy of positive landscape change – rather than attempts to stop change as in traditional preservationist approaches – requires the identification of threats and opportunities. Tools to do this will need to be based on well-investigated evidence for the long-term past evolution of landscapes and the understanding of possible future scenarios for change. Historic landscape characterisation (HLC) is a GIS-based method employed to interpret and study landscapes with a particular focus on representing and mapping the aspects of landscape character which result from past cultural processes. This paper introduces a new protocol which uses HLC data to model future landscape evolution and to simulate scenarios of landscape change. It describes a computer-based simulation framework derived from landscape ecology and used with HLC datasets during research on a region in southern Turkey. Such integrated modelling protocols have the potential to assist landscape planners to develop holistic and informative approaches to managing landscape change.